Answer:
3
Step-by-step explanation:
f(x) = 2x^2 + 1
f(-1) means that wherever you see an x on the right hand side, you substitute -1.
f(-1) = 2(-1)^2 + 1 = 2 + 1 = 3
Answer: It is B
Rae will ask 75 randomb students in her school
Step-by-step explanation:
honestly I just guessed, and got it right
9514 1404 393
Answer:
$1904.76
Step-by-step explanation:
The interest formula is ...
I = Prt . . . . interest on principal P at rate r for t years
Solving for P, we find ...
P = I/(rt) = 200/(0.07·1.5) = 200/0.105 ≈ 1904.76
The principal amount was $1904.76.
a+2 a +1
= ------- / ------------------
a -5 (a - 3)(a - 5)
a+2 (a - 3)(a - 5)
= ------- * ------------------
a -5 a +1
(a+2)(a - 3)
= ----------------
a +1
a NOT equal 5 and -1